IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TEAM GAMES TOURNAMENT DALAM MENINGKATKAN HASIL BELAJAR PAI SISWA KELAS VII SMP INTEGRAL MINHAJUTH THULLAB WAY JEPARA LAMPUNG TIMUR - Umi Syadiyah; Fitriyah Fitriyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Low learning outcomes in Islamic Religious Education (IRE) remain a challenge in the teaching and learning process, particularly due to the use of instructional models that have not effectively encouraged students’ participation and motivation. Although previous studies have shown that cooperative learning can improve learning outcomes, the implementation of the Team Games Tournament (TGT) model in IRE learning at SMP Integral Minhajuth Thullab Way Jepara, East Lampung, has received limited attention. Therefore, this study is important to examine the effectiveness of the TGT model in improving students’ learning outcomes. The objective of this study was to improve the IRE learning outcomes of seventh-grade students through the implementation of the Team Games Tournament (TGT) cooperative learning model. This study employed Classroom Action Research (CAR), conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 29 seventh-grade students. Data were collected through observation, interviews, documentation, and learning achievement tests, and were analyzed using quantitative and qualitative descriptive techniques. The results showed that the implementation of the Team Games Tournament (TGT) model improved students’ learning outcomes in Islamic Religious Education. The improvement was indicated by an increase in the number of students achieving learning mastery and a higher class average score in each cycle. These findings suggest that the TGT model creates a more active and collaborative learning environment, which positively contributes to students’ learning achievement. ABSTRAK Rendahnya hasil belajar Pendidikan Agama Islam (PAI) masih menjadi permasalahan dalam proses pembelajaran, terutama karena penggunaan model pembelajaran yang kurang mampu mendorong keaktifan dan motivasi siswa. Meskipun berbagai penelitian menunjukkan bahwa pembelajaran kooperatif dapat meningkatkan hasil belajar, penerapan model Team Games Tournament (TGT) pada pembelajaran PAI di SMP Integral Minhajuth Thullab Way Jepara Lampung Timur belum banyak diteliti. Oleh karena itu, penelitian ini penting dilakukan untuk menguji efektivitas model tersebut dalam meningkatkan hasil belajar siswa. Penelitian ini bertujuan untuk meningkatkan hasil belajar PAI siswa kelas VII melalui penerapan model pembelajaran kooperatif tipe Team Games Tournament (TGT). Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, meliputi tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian terdiri atas 29 siswa kelas VII. Data dikumpulkan melalui observasi, wawancara, dokumentasi, dan tes hasil belajar, kemudian dianalisis menggunakan teknik deskriptif kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa penerapan model Team Games Tournament (TGT) dapat meningkatkan hasil belajar PAI siswa. Peningkatan terlihat dari bertambahnya jumlah siswa yang mencapai ketuntasan belajar dan meningkatnya nilai rata-rata kelas pada setiap siklus. Dengan demikian, model TGT efektif dalam menciptakan pembelajaran yang lebih aktif dan mendukung peningkatan hasil belajar siswa.